2018
DOI: 10.1044/2017_jslhr-l-16-0409
|View full text |Cite
|
Sign up to set email alerts
|

Bilingualism and Procedural Learning in Typically Developing Children and Children With Language Impairment

Abstract: Procedural learning does not appear to be modified by language experience, supporting the notion that it is a child-intrinsic language learning mechanism that is minimally malleable to experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
0
13
0
1
Order By: Relevance
“…The task that we used was based on the one used by Lum and Kidd (2012). Lum and Kidd did not compare serial reaction time task performance between children with and without DLD, but task designs similar to the set-up of their task (see Introduction) have been used to assess the presence of a visuomotoric statistical learning deficit in children with DLD (Clark & Lum, 2017;Conti-Ramsden et al, 2015;Hsu & Bishop, 2014;Park et al, 2018). Unexpectedly, we observed that both groups of children were sensitive to the structural regularities, and we found no evidence for or against a difference in sensitivity between children with and without DLD.…”
Section: Discussion Experimental Studymentioning
confidence: 99%
See 4 more Smart Citations
“…The task that we used was based on the one used by Lum and Kidd (2012). Lum and Kidd did not compare serial reaction time task performance between children with and without DLD, but task designs similar to the set-up of their task (see Introduction) have been used to assess the presence of a visuomotoric statistical learning deficit in children with DLD (Clark & Lum, 2017;Conti-Ramsden et al, 2015;Hsu & Bishop, 2014;Park et al, 2018). Unexpectedly, we observed that both groups of children were sensitive to the structural regularities, and we found no evidence for or against a difference in sensitivity between children with and without DLD.…”
Section: Discussion Experimental Studymentioning
confidence: 99%
“…our conceptual replication) of the present study, we use a serial reaction time that is based on the one used by Lum and Kidd (2012, for differences between our task and the task of Lum and Kidd, see Materials section). We decided to work with this serial reaction time task as the design of this task is comparable, in terms of the sequence type used (first-order conditional) and the block structure used (structured versus random blocks), to serial reaction time tasks that are commonly used to assess the presence of a visuomotor statistical learning deficit in children with DLD (e.g., Clark & Lum, 2017;Conti-Ramsden et al, 2015;Hsu & Bishop, 2014;Park et al, 2018). Thus, our experimental study can be seen as a conceptual replication of earlier work on the presence of a visuomotoric statistical learning deficit in children with DLD.…”
Section: The Serial Reaction Time Taskmentioning
confidence: 99%
See 3 more Smart Citations